Six days : how the 1967 war shaped the Middle East - Bowen, Jeremy, 1960- (New York : Thomas Dunne Books, 2003)
"Suicide attacks on Israelis, bombings, assassinations, and bloodshed in Jerusalem, Gaza, and the West Bank dominate the news from the Middle East. It is the most troubled region on earth. At its heart is the conflict between Palestinians and Israelis - and the legacy of six days of war in 1967." "After the state of Israel emerged from war in 1948, both sides knew more battles were coming. In June 1967, years of slow-burning tension exploded. In six extraordinary days, Israel destroyed the armed forces of Egypt, Jordan, and Syria. But far from bringing peace, as many Israelis hoped, their stunning victory turned into a curse." "From the initial battle order issued to the Israeli air force on Monday June 5, 1967 to the final ceasefire on the evening of Saturday the 10th, the Six-Day War was a riveting human drama. Building on his first-hand experience of the region after his five years as the BBC's Middle East Correspondent, as well as extensive original research, Jeremy Bowen presents a new history of the conflict. Six Days recreates day by day, hour by hour, the bullying and brinckmanship that led four nations to war, interweaving testimonies of combatants from all sides." "Six Days not only sheds new light on one of the key conflicts of the twentieth century, it explains much about the Middle East and the problems the region still faces today."--BOOK JACKET.
Pre-war -- Day one: 5 June 1967 -- Day two: 6 June 1967 -- Day three: 7 June 1967 -- Day four: 8 June 1967 -- Day five: 9 June 1967 -- Day six: 10 June 1967 -- Consequences -- Legacy.
Includes bibliographical references (p. 405-410) and index.
Keywords: Israel-Arab War, 1967 -- Influence; x; Sechstagekrieg